Study of He-Ne Laser Beam Propagation Through Air and Pure, Salt (Still and Turbulence) Water (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This papers ,study  properties of the laser beam in the  different condition,  By using optical system consist of the (He- Ne) laser ((λ =632.8nm , p=1.04mw)), the parameter beam laser(spot, shape, intensity) were study and also study the attenuation and turbulence for the laser mentioned above and with following environmental condition.(1) in the air (2) in the pure ,slate (seawater)water with concentration 10-5Ml (still, turbulence)  at different distance. Measurement were obtained by using a CCD camera and silicon detector type(Silicon PIN) in fast response (.0.4-0.7)A/W, absorption coefficient value of all cases  was calculated.